An Overview of the Study of Language in the History of Philosophy (Renaissance to Postmodern) - Parlindungan Pardede (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
To English educators and researchers, having a good grasp of what a language is and how language learning takes place is important. To a certain extent, surveying language study development is a good start to achieving the goal. This article is the second part of a literature review summarizing language studies taking place along the history of philosophy that has lasted for 26 centuries, starting from ancient Greek to the postmodern era. This part includes language studies conducted in Renaissance Period up to the Postmodern Age. Data was collected by surveying relevant and credible textbooks and scientific articles. The findings reveal that unlike language studies in Ancient Greek up to the Middle Ages that focused on various paradigms related to the nature of language and micro-linguistic concepts, the studies in the era of modern philosophy focus on the relationship between language and users and the world. Overall, the changes in the focus of language studies over the 26 centuries indicate that the study of language will keep on going on and on because language is a symbiotic organism that continues to change along with the changes in thinking, experience, life, and human culture as the host of the symbiosis between language and humans.